TESTING TWO EXTENDERS AND CRYOPROTECTANTS FOR LONG-TERM PRESERVATION OF SHABOUT FISH’ SPERMS - & et al., Al-Mohammedi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The current study was conducted to test Shabout’s (Arabibarbus grypus) sperms ability for long-term cryopreservation under liquid nitrogen (-196ºC) using two different extenders and two different cryoprotectants to compare and chose the best. The semen of mature fishes collected from Al-Radwania man-made lakes during 2015 spring spawning season were used in this study. The semen was collected by manual abdominal stripping without using any hormones or anesthetizes and its sperms were tested for surviving and activity throw cryopreserving process in liquid Nitrogen using two different extenders (Zhang & Liu vs. Calcium-free Hank’s Balanced Salt Solution) with methanol in 10% as cryoprotectant for the first extender and glycerol in the same percent with the second and considering the motility rate as indicator for survival and activity during prefreezing and post thawing processes. The obtained quantities of semen ranged between 1-9 ml with mean volumes of 4.6 ml. Sperm motility rate using Zhang & Liu with 10% methanol was better in prefreezing diluents over Hank’s, its motility rates ranged between 80-95% with mean 87.5%, while Hank’s sperms motility results ranged between 50-95% with mean 69%. This situation was inverted after freezing and thawing, because Zhang and Liu solution lost 57.5% of its sperms motility while Hank’s with glycerol lost only 40%, thus Hank’s sperms motility mean reached 50% while Zhang and Liu was 30%. From these results we can infer that Shabout’s sperms has the ability to be cryopreserved in liquid Nitrogen and c-f Hank’s solution with 10% glycerol as cryoprotectant better than Zhang and Liu with methanol for long-term cryopreservation though, we can use Zhang and Liu solution also for short-term Shabout’s sperms cool preservation.